Aprendendo isometria com mosaicos - Rossi, Izabela Caroline [UNESP] (2014)
This work presents a proposal of activities aimed at teaching isometry using mosaics, especially the Escher's mosaics, which are results of pavings of the plane that have a certain pattern. It's a different way of teaching content, because instead of just using the traditional method of teaching, uses differentiated and playful materials, in addition to computing resources, which make much more attractive and motivating classroom, making the student feel more interest in participating in activities and assisting in his learning